Digital Illustrations in Journalism - Ragavan, V Saravana (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Since 1970’s artists were attracted towards computers and with the aid of Illustrators and Photoshop, illustrators were able to explore digital motifs and patterns. In the late 1980’s, illustrators blended the tools of drawing, painting, photography and software which resulted in perfect digital illustration. Later it is widely seen in print media and digital media around the globe. Today visual language is used over many different mediums, the language they have created by illustrated journalists are transformative catalyst for change as they present the complexities of a social issue, raise awareness and inspire action or thought. The digital era has given all creative people a great platform to explore their ideas. This paper focuses on the creative process, techniques and the experience from illustrator’s perspective. With the technological advancements, how far illustrations are narrative and innovative in the field of journalism will be discussed. The recent trends in digital illustration and its vital role in complementing journalism will also be highlighted. How to cite this article: Ragavan VS. Digital Illustrations in Journalism. J Adv Res Jour Mass Comm 2018; 5(4): 96-100. DOI: https://doi.org/10.24321/2395.3810.201825